The effect of weight training volume on hormonal output and muscular size and function - Ostrowski, K. J.; Wilson, G. J.; Weatherby, R.; Murphy, P. W.; Lyttle, A. D. (The Journal of Strength and Conditioning Research, 1997)
Ostrowski et al (1) compared the effects of three different weight training programs on muscle hypertrophy, strength, and power. 27 experienced male college-aged subjects participated in the study and were randomly assigned to three groups: a low volume group (3 sets per muscle group, each muscle group trained once a week), a medium volume group (6 sets per muscle group, each muscle group trained once a week), and a high volume group (12 sets per muscle group, each muscle group trained once a week). The only difference in the training protocols between the groups was the number of sets per exercise. No power exercises (such as cleans) were performed by the groups. The study lasted 10 weeks. Muscle size was measured via ultrasound, strength was measured via 1 RM bench press and 1 RM squat, and power was measured via vertical jump and bench press throw. Urinary concentrations of testosterone and cortisol were measured. FINDINGS: All three groups significantly improved in all measures except for vertical jump, but there were no significant differences between groups for any measure. Urinary testosterone/cortisol ratio showed a trend towards overtraining as training volume increased. IMPLICATIONS: Over a 10 week period, a resistance training program involving a low number of sets per exercise may be just as effective as higher volume programs in eliciting changes in muscle strength and size in experienced trainees. Coaches should not be afraid to reduce training volume, especially during the inseason when training time is minimized, since lower volumes of training appear to not be detrimental to performance. While the high volume group showed a hormonal trend towards overtraining, these results should be viewed with caution, because urinary concentrations of hormones were measured, which may not reflect blood levels. A resistance training program that does not include power movements may not be effective for increasing vertical jump in trained individuals.